India Connects to Wireless Internet. - Singh, S.
WiMax technology offers the possibility for many Indians to wirelessly connect to high-speed Internet without the need for DSL links and cable modems. While many businesses recognize the potential, the Indian government has been slow to allocate spectrum for WiMax. As an alternative, vendors are looking at the subgigahertz band subject to ratification by the WiMax Forum, a consortium of WiMax equipment and service providers. Despite the uncertainties, there is no doubt that India can contribute significantly to future versions of wireless broadband technology
Keywords: DSL links; Indian government; WiMax technology; Cable modems; Service providers; Wireless Internet; Wireless broadband technology